Hubungan Asupan Natrium Dan Kalium Dengan Tekanan Darah Pada Lansia Di Kelurahan Pajang - Susanti, Mike Rahayu, Muwakhidah, S.KM, M.Kes, Wahyuni, S.KM, M.Kes (2017)
Background : High blood pressure (hipertention) is caused by retention of sodium in the circulation. Potassium can lower blood pressure by promote vasodilatation of blood vessel thus resulting in total peripheral retention. Based on the preliminary survey, prevalence of hipertention in Pajang village has 19%. Objective : To determine the association of sodium and potassium intake to blood pressure in elderly at Pajang village. Research Method : This study is an observational study with cross-sectional approach. A to the of 64 subjects were recruited using multistage sampling. Data of sodium and potassium intake were obtained using semi quantitative food frequency. The data of blood pressure were obtained using sphygmomanometer. All data were analyzed using Spearman Rank correlation. Result : This result show that 35 subjects (66%) have high sodium intake, 53 (100%) have low potassium intake, 34 subjects (64,2%) have high sistolic blood pessure and 28 (52,8%) have high diastolic blood pressure. There is an association of sodium intake to systolic (p=0,040) and diastolic (p=0,041) blood pressure. There is no association of potassium intake to systolic (p=0,478) and diastolic (p=0,203) blood pressure. Conclusion : There is an association of sodium intake to blood pressure in elderly in the Pajang village. There is no association of potassium intake with blood pressure in elderly in the Pajang village.